Supplementation of high-quality fresh forage to lambs fed a total mixed ration increased in vitro ruminal fermentation and digestibility - Pérez-Ruchel, Analía; Repetto, José Luis; Cajarville, Cecilia (Frontiers in Animal Science, 2023)
The effect of supplementing fresh alfalfa, to growing lambs fed with decreasing levels of total mixed ration (TMR) was studied on in vitro ruminal fermentation activity. Twenty-four catheterized lambs (25.2 ± 3.67 kg BW), were assigned to the treatments: ‘TMR100’: TMR ad libitum; ‘TMR75’ and ‘TMR50’: TMR at 0.75 and 0.50 of potential intake, respectively, complemented with alfalfa; ‘TMR0’: only alfalfa ad libitum. In vitro gas production kinetics and true digestibility (IVTD) were evaluated using the rumen liquid as inocula. Ruminal pH, NH3-N and volatile fatty acids concentrations were studied at the same time as inocula extraction. As the amount of alfalfa in the diet increased - by decreasing the level of TMR - in vitro gas production, ruminal pH, NH3-N concentration and acetic acid proportion linearly increased (p = 0.005, 0.008, 0.004, 0.018, respectively), IVTD tended to linearly rise (p = 0.083) and the fermentation rate (p = 0.004) and propionic acid proportion (p < 0.001) linearly decreased. We conclude that the increase in the level of fresh alfalfa derived by the decrease of TMR levels in lamb’s diet positively impacted rumen fermentation activity and in vitro digestibility through the promotion of a suitable environment for ruminal microbiota.